2023
DOI: 10.1002/pld3.518
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis in multiple barley varieties identifies signatures of waterlogging response

Abstract: Waterlogging leads to major crop losses globally, particularly for waterlogging‐sensitive crops such as barley. Waterlogging reduces oxygen availability and results in additional stresses, leading to the activation of hypoxia and stress response pathways that promote plant survival. Although certain barley varieties have been shown to be more tolerant to waterlogging than others and some tolerance‐related quantitative trait loci have been identified, the molecular mechanisms underlying this trait are mostly un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…Likewise, short term waterlogging stress in Franklin and TX9425 barley cultivars, revealed higher representation of terms in metabolism modulation, catalytic activity and oxidation-reduction processes (Luan et al, 2023). This, together with observed significant overlap with core transcriptional response to waterlogging defined for barley by Miricescu et al (2023) (Table S4A, 4B), places this research within the established literature on general transcriptomic responses in barley to waterlogging.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Likewise, short term waterlogging stress in Franklin and TX9425 barley cultivars, revealed higher representation of terms in metabolism modulation, catalytic activity and oxidation-reduction processes (Luan et al, 2023). This, together with observed significant overlap with core transcriptional response to waterlogging defined for barley by Miricescu et al (2023) (Table S4A, 4B), places this research within the established literature on general transcriptomic responses in barley to waterlogging.…”
Section: Discussionsupporting
confidence: 66%
“…However, while there were large differences in basal (control) gene expression between Franklin and Yerong at both 24 and 72 h, they provided putative explanation for only between 9 and 26 % of cultivar specific differences in gene expression in response to waterlogging (Figure S3). The transcriptional signature induced by waterlogging stress in this study was also compared to the list of core waterlogging-response genes recently identified by Miricescu et al (2023), revealing a significant overlap and strong association between the response observed for both cultivars and at both time points (Table S4A), with the same direction of regulation (Table S4B) . Collectively, generated data underscore that both core and cultivar specific responses to waterlogging stress exist and need to be further dissected to elucidate transcriptional signatures related to waterlogging tolerance and sensitivity.…”
Section: Root System Adaptations Mediating Waterlogging Tolerance In ...mentioning
confidence: 68%
See 3 more Smart Citations